The Influence of the Role of Islamic Financial Institutions on Optimizing Islamic Economic Policy Through Increasing Productive Financing in Bangka Belitung Province - Efendi Sugianto; Mohamad Makrus; Afrizal Afrizal (Pt. Anagata Sembagi Education, 2025)
This study aims to analyze the influence of Islamic financial institutions (IFIs) on the optimization of Islamic economic policy through increased productive financing in the Bangka Belitung Islands Province. The background to this study is the low proportion of productive financing channeled by IFIs, as most funds are still focused on the consumer sector and therefore do not contribute optimally to regional economic development. Using a quantitative approach with the Structural Equation Modeling (SEM) method, the study involved 120 respondents consisting of ISI employees, customers, MSME actors, and regional policy makers. The results show that the role of ISIs has a positive and significant effect on increasing productive financing with a regression coefficient of 0.68 and significance below 0.05. Productive financing also has a significant effect on the optimization of Islamic economic policy with a regression coefficient of 0.72 and an R² value of 0.73. The variable of productive financing plays an important mediating role in strengthening the relationship between the role of LKS and Islamic economic policy, particularly through the MSME, agriculture, and fisheries sectors. These findings confirm the relevance of Islamic finance theory and the principles of maqashid al-syariah, and emphasize the importance of synergy between the government, Islamic financial institutions, and the community in building a fair, inclusive, and sustainable Islamic economic ecosystem